STRATEGI PEMBELAJARAN BAHASA INDONESIA (TINJAUAN STUDI KASUS DI SMK MADINATUL HADID CILEGON) - Mahpudoh Mahpudoh; Diana Romdhoningsih; Andrean Andrean; Ismail Fahmi (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
This study aims to analyze the implementation of Indonesian language learning strategies at SMK Madinatul Hadid Cilegon, focusing on communicative approaches, the use of technological media, and project-based learning. The method used in this research is a descriptive qualitative approach with data collection through interviews, observations, and documentation. The results of the study indicate that the implementation of these learning strategies has a positive impact on students' speaking and writing skills, although there are challenges such as differences in students' confidence levels, limited technological facilities, and limited time to complete projects. Technology and project-based learning increase student participation but require adjustments in time and facility management. The conclusion of this study is the importance of improving supporting facilities, more structured time, and special attention to students who have difficulty participating actively. This research provides prospects for further development regarding the application of technology in learning and the importance of external support in the success of Indonesian language learning